Comparison between Broadrick flag Vs Yurkstas metal occlusal template in the assessment of mandibular Over-erupted teeth - Zahra Alsaileek; Najwa Alqurayqiri; Mahmoud Elsamahi (Wolters Kluwer Medknow Publications, 2019)
Introduction: An occlusal plane analyzer has long been used to assist an operator in the development of an initial mandibular occlusal plane in diagnostic contour casts and later as an integral part of both the contours of the definitive restorations as guide for the actual tooth preparation. Broadrick and Yurkstas metal occlusal template were devices frequently used to determine the proper occlusal plane. Aim: The aim of this study was to determine which of the two methods. Broadrick flag occlusal plane analyzer or Yurkstas metal occlusal template is more conservative during occlusal plane adjustment. Materials and Methods: Eight diagnostic casts mounted on Hanau semi-adjustable articulator were selected from the casts of patients of undergraduate 6th-year dental students, King Abdulaziz University. Diagnostic maxillary cast was mounted according to arbitrary ear-bow and the mandibular casts were mounted according to centric relation records. First, Broadrick occlusal plane analyzer was secured to the upper member of the articulator. The anterior and posterior survey points were drawn. From the intersection point, the anteroposterior curve was drawn on the buccal surfaces of the canine, premolar, and molar. The distance from these lines to the cusp tip was measured through mesiobuccal, midbuccal, and distobuccal areas. Yurkstas metallic occlusal plane was used in the second method. The articulating paper horseshoe was placed between the occlusal table of the stone teeth and the metallic template, and the articulator was closed and taped several times, a die marking indicating the first over-erupted teeth. Then the highlighted area was reduced to 1 mm. The procedure was repeated until a uniform touch of the template over the mandibular teeth was maintained. Finally, the amount of reduction was collected. Conclusion: Producing curve of Spee is more conservative while using Yurkstas metallic occlusal plane.